Real-Time Monitoring and Development of a Localized OTTV Equation for Building Energy Performance - Vighio, Anees A.; Zakaria, Rozana; Ahmad, Faridahanim; Aminuddin, Eeydzah (Civil Engineering Journal, 2025)
Global warming negatively impacts indoor environments, affecting human comfort. Despite global efforts, energy demand and greenhouse gas emissions continue to rise. As sustainable building designs become more critical, enhancing energy efficiency through real-time data analytics is essential. The Overall Thermal Transfer Value (OTTV) is a key metric for assessing a building’s energy usage, considering factors like orientation, location, and climate. However, limited research has examined real-time data's impact on OTTV coefficients. Therefore, this research aims at developing and validating new OTTV coefficients using real-time data with the EQUEST simulation engine. The coefficients of OTTV (Equivalent Temperature Difference TDeq, Temperature Difference ∆T, and Solar Factor SF) were monitored in real-time using HOBO Temperature Data loggers and Delta Ohm Photometer for Solar Radiations. Focusing on UTM Eco-Home building, the study calculates heat gain components, including transmission through walls, windows, and radiation heat gain. The findings of the study suggest that the modified OTTV equation accurately determines a building's OTTV, enhancing energy efficiency evaluations. The novelty of the study lies in the development of a new OTTV equation for the specific climate of Johor, Malaysia, and the real-time monitoring of OTTV that helps the energy managers analyze the Thermal Transmittance of Building envelopes in real-time. Doi: 10.28991/CEJ-2025-011-02-09 Full Text: PDF